A possible way to naturalize the human soul - Guijarro Morales, José Luis (Pragmalingüística, 2009)
<!-- [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabla normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif]--> One of the most basic linguistic principles (or parameters, according to some) is used to point to a likely necessary (though, probably, not sufficient) condition of human uniqueness (i.e. being able to speak, communicate complex messages, have religious feelings, indulge in art and humour, and so on) which has been conceptualised either as the fact that we have human souls, in religious contexts, or human minds, in other contexts.